Abstracts of oral and poster presentations given at the 12th International Workshop on Grapevine Trunk Diseases, Mikulov, Czech Republic, 10–14 July 2022 - VV., AA. (Phytopathologia Mediterranea, 2022)
The 12th International Workshop on Grapevine Trunk Diseases (12th IWGTD) was held in Mikulov, Czech Republic, from 10 to 14 July, 2022. The Workshop was chaired by Dr Aleš Eichmeier and organized by Mendel University in Brno and Svaz Vinařů České Republiky/Union of Winemakers of the Czech Republic. The ICGTD Council meeting took place on 10 July, and that evening the welcome reception was opened by Rostislav Koštial (Mayor of Mikulov, Senator and viticulturist), Dr Martin Chlad (President of Svaz Vinařů České Republiky/Union of Winemakers of the Czech Republic), and Dr Svatopluk Kapounek (Vice-Rector, Mendel University, Brno). The scientific programme was opened by Dr Alena Salašová (Dean, Faculty of Horticulture, Mendel University, Brno). The Workshop was attended by 133 researchers from 25 countries, presenting 61 oral and 49 poster papers. These presentations were in five sessions, including; Pathogen Characterization and Identification, Epidemiology, Plant-pathogen Interactions, Microbial Ecology, and Disease Management in Nurseries and Vineyards. The Disease Management session aimed to provide grape growers with an overview of practical options for trunk disease control. This session included contributions from researchers who have completed field trials on trunk disease management. David Gramaje (Instituto de Ciencias de la Vid y el Vino (ICVV), Logroño, La Rioja, Spain, outlined an evaluation of treatments for protection of grapevine pruning wounds from natural pathogen infections; Francois Halleen (University of Stellenbosch, South Africa) presented detailed results of efficiency of hot water treatments in nurseries; and Josè Úrbez-Torres (Agriculture and Agri-Food Canada SuRDC) outlined research on biological control of Botryosphaeria dieback in grapevines. A field trip (13 July) visited vineyards in the South Moravia. Delegates were presented with an overview of grapevine production in South Moravia, followed by discussions on the main diseases (including GTDs) affecting grapevines in the Czech Republic. Vineyards affected by GTD pathogens were also visited, where the growers outlined their viewpoints. The field trip focused on presenting the current situation of GTDs in South Moravia, and the management strategies being adopted. Student competitions for best oral and poster presentations included papers presented by 29 postgraduate students. For best posters: 1st place went to Catarina Leal (University of Reims Champagne-Ardenne, France, and Polytechnic University of Valencia, Spain), “Evaluation of Trichoderma atroviride SC1 and Bacillus subtilis PTA-271 combination against grapevine trunk diseases pathogens in nursery propagation process”; 2nd place went to Marcelo Bustamante (University of California, Davis, United States of America), “Investigating the role of Fusarium spp. in young vine decline in California”; 3rd place went to María Julia Carbone (Universidad de la República, Montevideo, Uruguay), “Interactive effects of Dactylonectria macrodidyma inoculation on the rhizosphere and root microbiome of grapevine”. For best oral presentations: 1st place went to Catarina Leal, (University of Reims Champagne-Ardenne, France, and Polytechnic University of Valencia, Spain), “Beneficial effects of Bacillus subtilis PTA-271 and Trichoderma atroviride SC1 against the Botryosphaeria-dieback pathogen Neofusicoccum parvum may vary with grapevine cultivar”; 2nd place went to Isidora Silva-Valderama (University of British Columbia, Vancouver, Canada), “Predicting pathogens virulence: linking host breadth and pathogenicity of the Botryosphaeriaceae fungal family in wine grapes (Vitis vinifera)”; 3rd place went to Colin Todd (University of California, Riverside, United States of America), “Tracking the fungal pathobiome associated with young grapevine decline in California nurseries”. The 13th IWGTD will be held in Ensenada, Mexico, in 2025.